Preparation and Investigation of the Mechanical and Thermal Properties of Styrene Butadiene Rubber using Dicumyl Peroxide as Curing Agent - Liem, Nguyen Thanh; Tung, Nguyen Huy; Linh, Nguyen Pham Duy; Phuc, Banh Trong; Thuy, Nguyen Thi; Chuong, Bui (VNU Journal of Science: Natural Sciences and Technology; Vol 36 No 2DO - 10.25073/2588-1140/vnunst.4997, 2020)
This paper investigates the mechanical and thermal properties of styrene butadiene rubber (SBR) using dicumyl peroxide as curing agent. The results showed that the tear strength of SBR with 2 phr DCP as curing agent increased sharply from 31,7 N/mm to 73,2 N/mm compared to SBR cured with sulfur. The other mechanical properties like tensile strength, elongation at break are unchanged. The accelerators DM/TMTD used by curing of SBR have not only influence on mechanical properties but also on the curing time. Using 0.5-phr trimethylolpropane trimethacrylate (EM 331) also increases the thermal stability of SBR, thermal aging ratio reaches 0.79 from 0.66 comparing with sample without EM 331. Nano silica have good effec for  thermal conductivity coefficient of SBR . At the nano silica content of 3% the thermal conductivity coefficient increases by more than 20.68%, from 0.672 W / m * K of SBR to 0.811 W / m * K of SBR/nano silica composite. This will probably have a good effect on properties of finished product when blending SBR rubber with other types of synthetic rubber which have different vulcanizing properties.